The use of cyclic peptide antigens to generate LRP8 specific antibodies - Argiriadi, Maria A.; Deng, Kangwen; Egan, David; Gao, Lei; Gizatullin, Farid; Harlan, John; Karaoglu Hanzatian, Denise; Qiu, Wei; Villanueva, Ruth; Goodearl, Andrew (Frontiers in Drug Discovery, 2023)
LRP8 is a member of the LDLR-like protein family. It is a transport receptor, which can be used in the design of antibodies specific for investigating increasing exposure to therapeutics with respect to the blood brain barrier (BBB). In this study, a LRP8 peptide immunization strategy was implemented to generate antibodies to a specific epitope of the CR1 domain of LRP8 that could enable transport function and cross-react in mice, cynomolgus monkeys and humans. Additionally, a cyclized peptide immunogen was designed to conserve the structural β-hairpin element observed in a previously solved crystal structure of a related CR domain. As a result of this structure-based antigenic design, an LRP8 specific antibody, 11H1, was selected and characterized in ligand binding assays and crystallographic structure determination. The high-resolution structure of the 11H1 Fab complexed to the cyclized CR1 peptide revealed key interactions driving epitope recognition that were confirmed using a site-directed mutagenesis approach. A critical observation was that the identified structural CR1 epitope of 11H1 did not compete with reelin’s recognition of CR1 allowing for simultaneous binding. This was predicted by an in silico ternary model and confirmed by reelin binding data. These simultaneous binding events (11H1/CR1/reelin) could therefore enable the CR1 domain of LRP8, 11H1 and reelin to be used as a “BBB transporter” ternary complex in the design of therapeutic proteins. More importantly, 11H1 showed enhanced brain penetration after systemic intravenous dosing in a mouse study, which confirmed its potential function as BBB transporter for therapeutic proteins.